Optimal financial contracting and the effects of firm's size - Sandro Brusco; Giuseppe Lopomo; Eva Ropero; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2024)
We consider the design of the optimal dynamic policy for a firm subject to moral hazard problems. With respect to the existing literature we enrich the model by introducing durable capital with partial irreversibility, which makes the size of the firm a state variable. This allows us to analyze the role of firm's size, separately from age and financial structure. We show that a higher level of capital decreases the probability of liquidation and increases the future size of the firm. Although analytical results are not available, we show through simulations that, conditional on size, the rate of growth of the firm, its variability and the variability of the probability of liquidation decline with age.
Additional information: Revised version - July 2020
Keywords: 330